Duodenal obstruction due to missed pre-duodenal portal vein in a patient with intestinal malrotation - Stephen Akau Kache; Danjuma Sale; Victoria Ijeoma Chinwuko; Philip Mari Mshelbwala (Wolters Kluwer Medknow Publications, 2022)
Pre-duodenal portal vein (PDPV) is a rare anomaly and a rare cause of duodenal obstruction (DO), with only a few cases reported in the literature. We present an infant whose bilious vomiting persisted despite having Ladd's procedure for intestinal malrotation due to a missed diagnosis of DO from PDPV that was found at re-exploration. The patient was diagnosed with malrotation and had Ladd's procedure at 12 weeks of age, but bilious vomiting persisted post-operatively. The patient presented to us after 4 weeks, was clinically malnourished and dehydrated, resuscitation was done and re-exploratory laparotomy performed, where an obstructing PDPV was found and a duodeno-duodenostomy was performed anterior to PDPV. However, the patient died on post-operative day 7 probably from severe malnutrition due to delayed diagnosis and absence of parenteral nutrition. We conclude that PDPV may be a cause of DO in infants with malrotation and should be properly sought for during Ladd's procedure for possible bypass surgery if found.